NEW APPROACH ABOUT NEOTROPICAL HELMINTHOLOGY - Cárdenas-Callirgos, Jorge (2008)
Helminths are a group of invertebrates of major scientific interest due to their high impact on public health and the diverse evolutionary histories that some of its members have followed in order to adapt to the parasitic lifestyle. In the Neotropical region, though, helminth research has been traditionally associated with their effect on public health. This topic awaits more reflection and political support for its beneficial implementation, especially in rural zones where the prevalence of infection by helminth parasites in humans can be very high (Cabrera, 2003).